Corporate Social Responsibility and the influence of organisational communications on employee engagement: A case study of Experian (UK) plc. - Meader, Lesle J. (2009)
This report aims to build on previous research centred on the impact of CSR on employee behaviours and explore the role of communications in this model (Bhattacharya et al, 2008: Gond et al, 2006). The report evaluates the theoretical arguments in the literature review section by correlating the theory to the data collected from within the case study company. Principally the data comes from employee opinions and perceptions of the company‟s CSR strategy, and the communications pertaining to the CSR strategy using semi-structured focus groups. A meta analysis of a recent (2009) employee survey from the company as well as a desk top analysis of various company documents provide a contextual analysis of the company. Insights from social identity and signalling theory are used to correlate the finding highlighting the complex relationship employees have with their company. The report assesses the impact of a recent communications campaign which rolled-out the company CR Report (2009) to all employees to identify the impact of the communication on employees‟ engagement behaviours. The research identified that due to the use of a company intranet communication medium, the employees missed the communication and remained largely unaware of the company CSR strategy. The conclusions identify that employees are likely to have a stronger identification with internal CSR over external CSR activities. They also find that the employees of the case study company do not perceive their engagement to be affected by the CSR activities. However, the employees do concede that were the organisation to engage in irresponsible or unethical practices it is likely that this would negatively affect their feelings of organisational commitment and engagement. The recommendations propose improvements to the internal communications strategy and make further recommendations to link the strategies of HR, CSR and Communication functions to determine a „sustainability‟ strategy with a greater focus on internal CSR in order that the company might benefit from greater levels of engagement; organisational commitment and advocacy behaviours.